Desenvolvimento de biossensores à base de filmes poliméricos, nanotubos de carbono e nanopartículas de ouro - Vicentini, Fernando Campanhã (Universidade Federal de São Carlos, 2013)
In this work was described the development of new architectures for biosensors, using nanomaterials. The enzyme of interest was immobilized on glassy carbon electrode modified with multi-walled carbon nanotubes chemically treated and/or gold nanoparticles within a dihexadecylphosphate or poly(allylamine hydrochloride) film. Initially, a glassy carbon electrode (GCE) modified with functionalized multi-walled carbon nanotubes (MWCNTs), 1-butyl-3-methylimidazolium chloride (BMIM) and tyrosinase (Tyr) within a dihexadecylphosphate (DHP) film for the development of a biosensor was proposed. MWCNTs, BMIM and Tyr were efficiently immobilized in the film using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide/N-hydroxysuccinimide as crosslinking agents. The film characterization was realized by cyclic voltammetry (CV) in presence of catechol. The BMIM-MWCNTs nanocomposite showed good conductivity and biocompatibility with Tyr enzyme, once that the biosensor presented biocatalytic activity to the oxidation of catechol to o-quinone which was electrochemically reduced to catechol at a potential of 0.04 V. The Tyr-BMIMMWCNTs- DHP/GCE biosensor showed wide linear range, good repeatability, sensitivity and stability and, the biosensor was successfully applied in the determination of catechol in natural water samples. The second developed biosensor was based on the modification of a GCE with gold nanoparticles (AuNPs) and Tyr within a DHP film. The enzyme immobilization was performed using cystamine and glutaraldehyde as crosslinking agents. Amperometry technique was used to obtain the analytical curve that showed linear in the concentration of catechol in the range from 2.49 × 10−6 to 9.50 × 10−5 mol L−1 with a detection limit of 1.74 × 10−7 mol L−1. The Tyr-AuNPs-DHP/GCE biosensor was applied in the determination of catechol in water samples from the UFSCar Dam. The results were satisfactory when compared with a spectrophotometric method at a 95% confidence level. Finally, the modification of a GCE with MWCNTs and AuNPs within a poly(allylamine hydrochloride) (PAH) film for the development of a novel biosensor was proposed. This approach provided an efficient method used to immobilize polyphenol oxidase (PPO) obtained from the crude extract of sweet potato (Ipomoea batatas (L.) Lam.). The principle of the analytical method is based on the inhibitory effect of sulfite on the activity of PPO, in the reduction reaction of o-quinone to catechol and/or the reaction of o-quinone with sulfite. Under the optimum experimental conditions using the differential pulse voltammetry technique, the analytical curve obtained was linear in the concentration range of sulfite from 5.0 × 10−7 to 2.2 × 10−5 mol L−1 with a detection limit of 4.0 × 10−7 mol L−1. The biosensor was successfully applied in the determination of sulfite in white and red wine samples with results in close agreement with those results obtained using a reference iodometric method at a 95% confidence level.
Biosensors development based on polymeric films, carbon Nanotubes and gold nanoparticles
Keywords: Química analítica; Biosensores (Biossensores); Filmes poliméricos; Nanotubos de carbono; Nanopartículas de ouro; CIENCIAS EXATAS E DA TERRA::QUIMICA